(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2023)
The study was conducted to establish the effect of fish farming on plankton communities, water quality and sediment in Barobo Coastal Waters in Lianga Bay Philippines. Plankton, water, and sediment samples were collected during northeast monsoon period (November, December, and February) within the fish farms; transition zone (in-between fish farm and outside) and outside the mariculture zone. Two stations were established per zone. Results showed that a total of 245 taxa, 66 genera and 90,532 individuals of phytoplankton, while zooplankton had 306 taxa, 192 genera and 10,984 individuals were recorded across sampling stations for the entire sampling periods. There were no significant differences except for abundance/richness noted on the diversity of both phytoplankton and zooplankton communities between stations indicating that mariculture activities have no effects on the plankton communities. For the water quality parameters, water temperature, salinity, ammoniacalN, dissolved organic phosphorous and potassium did not vary significantly (p>0.05) while pH, transparency, velocity, DO and TSS vary significantly (p<0.05) between the stations. For the sediments, only N2 (p=0.051) showed no significant difference while the rest of the parameters such as pH (p<0.000), texture (p<0.000), Organic Matter % (p<0.000), available P (p<0.000) and extractable K (p<0.000) showed significant differences between stations. Most of the physicochemical parameters of water and sediments were significantly higher than the transition and outside mariculture zones which indicates that the water and sediment quality measured within the fish farm area were deteriorating. This finding may also imply that transition and outside mariculture zone has not yet affected by the fish farming activities. Despite the low degree of impact detected within the mariculture zone, the organic matter carrying capacity should be carefully determined to avoid environmental drawbacks, thus regular monitoring on the sediment and water quality is recommended.